Begawe Merariq as a Cultural–Religious Institution: Gender Roles and the Integration of Islamic Values in Sasak Wedding Traditions - Rihal Jayadi; Baiq Hapipah; Sri Rejeki Sri; Wahyu Azwar (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2025)
This study aims to examine the Begawe Merariq tradition of the Sasak community in Lombok by analyzing the integration of Islamic values and the gendered division of roles within the ceremonial process. The research focuses on how men’s and women’s roles are structured, legitimized, and sustained through customary norms and religious principles. The research employs a descriptive qualitative approach to explore social realities as they occur within the community. Data were collected through direct observation, in-depth interviews, and documentation. Informants were selected using purposive sampling, involving traditional leaders, community leaders, youth leaders, and male and female chefs who actively participate in Begawe Merariq activities. Primary data were complemented by secondary data obtained from relevant scholarly literature. Data analysis was conducted using the interactive model developed by Miles and Huberman, which encompasses data collection, data reduction, data display, and conclusion drawing. The study's results indicate that Begawe Merariq functions as a cultural and religious institution that structures collective participation and strengthens social cohesion. Men mainly undertake public decision-making, coordination, and physically demanding tasks, while women play strategic roles in preparation, hospitality, and consumption management at later stages of the ceremony. This complementary division of labor is rooted in Sasak customs and Islamic ethical values, enabling the tradition to sustain cultural continuity amid social change.